2020
DOI: 10.1007/s11156-020-00936-3
|View full text |Cite
|
Sign up to set email alerts
|

Do corporate insiders trade on future stock price crash risk?

Abstract: We explore whether firm managers trade on future stock price crash risk. This depends on managers’ ability to assess future crash risk, and on whether the expected payoff is greater than the expected costs associated with potential reputation loss and litigation risk. We find that insider sales are positively associated with future crash risk, which is consistent with managers’ trading on crash risk for personal gain. We also find that managers take advantage of high information opacity to pursue crash-risk-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 77 publications
5
46
0
Order By: Relevance
“…Insiders have information that is not yet publicly available, which can be used to assess the value of the company and predict future firm performance [34]. Insider sell-off behavior is positively associated with the risk of a stock price crash [35]. e insider's choice to sell stocks sends negative signals to outside investors, thereby raising the probability of a future crash risk.…”
Section: Theory and Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Insiders have information that is not yet publicly available, which can be used to assess the value of the company and predict future firm performance [34]. Insider sell-off behavior is positively associated with the risk of a stock price crash [35]. e insider's choice to sell stocks sends negative signals to outside investors, thereby raising the probability of a future crash risk.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…ey acquire and process data about firms using public information, field research, and other sources and reduce information asymmetry between firms and investors [37,38]. According to He et al [35], analyst coverage reduces stock price crash risk via analysts' role as information intermediaries and monitors. Nonetheless, when analysts cannot fully perform the information intermediary role, it is more difficult for investors to learn the real situation of the firm and they cannot accurately identify the noise in the media coverage; thus, the impact of media sentiment on future stock price risk is more evident through driving the investors' decision-making process.…”
Section: Theory and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…According to empirical evidence, it was found that proxy variables of information diffusion would exert a great influence on stock price fluctuations [11][12][13]. In particular, the dramatic diffusion of released bad news would lead to an increase in the stock price fall [3,14]. However, issues such as how information diffusion affects the stock market and how to quantify such effects remain unknown [15].…”
Section: Related Literaturementioning
confidence: 99%
“…However, it is prone to crises, especially stock price crash risk, because of the high sensitivity and volatility. As shown in prior studies, one of the fundamental causes of stock price crash risk is owed to the bad news hoarding [1][2][3]. Concretely, there exists a critical threshold at which it is too costly for management to withhold the bad news.…”
Section: Introductionmentioning
confidence: 97%